HUBUNGAN MUTU PELAYANAN AKADEMIK DAN DISIPLIN KERJA DOSEN DENGAN KEPUASAN MAHASISWA FKIP - UKI JAKARTA - Herlina Sianipar (Jurnal Pro-Life, 2014)
The research is aimed at revealing the relationship between the academic quality service (X1) and lecturer's work discipline (X0) with the students' satisfaction (Y) of Faculty of Education and Teacher's Training, Christian University of Indonesia, Jakarta. The research was conducted on the sixth semester students of the faculty of Education and Teachers Training, Christian University of Indonesia. Sixty students were taken samples with random sampling technique. The independent variable of this research is academic service quality (X1) and lecturers' work discipline (Y0), and the dependent variable is students' satisfaction (Y). The research was descriptively analyzed using survey method and correlation techniques. The data were collected through questionnaires with likert scale, each of which consists of 35 items. The calculation of the validity and reliability revealed 28 items of X1, 26 items of X2, and 29 items of the questionnaires. The analytical requirement was tested using Liliefor's normality test. The result shows that data were normally distributed the regression linearity test also reveals a linear regression. Based on the analysis result it is concluded that the academic quality service contributed 40,1 % to the students' satisfaction the lecturer's work discipline contributed 47%, while the academic quality service along with the lecturer's work discipline contributed 61, 7% to the student's satisfaction.